2016
DOI: 10.1007/s11032-016-0503-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo sequencing and characterization of seed transcriptome of the tree legume Millettia pinnata for gene discovery and SSR marker development

Abstract: Pongamia (Millettia pinnata) is a promising biofuel crop with multiple merits. Breeding of ideal Pongamia germplasm for industrial application demands substantial progress in molecular biology of this legume species, which has been largely hampered by the paucity of its genomic data. In this study, we constructed and characterized a comprehensive seed transcriptome by the high-throughput Illumina sequencing technology. We obtained over 83 million high-quality reads, which were processed and assembled into 53,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 67 publications
2
27
1
Order By: Relevance
“…Further, Pavithra et al 20 , reported the FA profiles of seeds at different developmental stages of Pongamia. Very recently, parallel to the current study, Huang et al 21 , reported the seed transcriptome of Pongamia which provided valuable information about lipid biosynthetic genes and SSR markers. But the whole transcriptome information, together with gene expression patterns of lipid biosynthetic enzymes during seed development and flowering pathway genes, are far from being characterised in Pongamia.…”
supporting
confidence: 59%
“…Further, Pavithra et al 20 , reported the FA profiles of seeds at different developmental stages of Pongamia. Very recently, parallel to the current study, Huang et al 21 , reported the seed transcriptome of Pongamia which provided valuable information about lipid biosynthetic genes and SSR markers. But the whole transcriptome information, together with gene expression patterns of lipid biosynthetic enzymes during seed development and flowering pathway genes, are far from being characterised in Pongamia.…”
supporting
confidence: 59%
“…This may be because they all belong to the family Fabaceae and share a high level of genomes sequence similarity. Similar observations have been reported on other transcriptome studies [41,42]. It is thought that KEGG provides a basic platform for systematic analysis of gene function in terms of gene product networks [43].…”
Section: Transcriptome Sequencing De Novo Assembly and Annotation Fsupporting
confidence: 83%
“…Therefore, the development of a known polymorphic SSR marker database for D. odorifera is of great use for diversity studies and breeding programs, as well as being transferable to closely Dalbergia species. In the present study, we identified 35,774 putative SSRs from the transcriptome dataset, which is of great differences in numbers, dominant repeats, and motif types reported from other legume species using Illumina sequencing [41,42,44]. This may be attributable to inconsistencies in genome structure or composition, dataset size, search method, or criteria.…”
Section: Ssr Prediction Validation and Applicationmentioning
confidence: 94%
“…In this study, we have identified 35,774 putative SSR loci from the leaf transcriptome dataset, substantially more than those reported for other legume species such as 5956 in Prosopis alba Griseb. [36], 5710 in Millettia pinnata (L.) Panigrahi [18], and 7493 in Mucuna pruriens (L.) DC. [37].…”
Section: Development Of Ssr Marker For D Odoriferamentioning
confidence: 99%
“…The use of microsatellite markers to analyze the genetic diversity of D. odorifera can provide an invaluable means for conservation and protection of this endangered species. Moreover, the developments of SSR markers have been innovated by next-generation sequencing based on transcriptomes (RNA-seq), especially for species without a reference genome [17][18][19]. This approach has been applied for SSR identification, development, and association studies in many tree species [20][21][22].…”
Section: Introductionmentioning
confidence: 99%